Largemouth Bass Hatchery Contributions Quantified via Parentage‐Based Tagging. (31st March 2022) - Hargrove, John S.; Dockendorf, Kevin J.; Potoka, Kathryn M.; Smith, Christopher A.; Alvarez, Valentina; Austin, James D.
Abstract: Largemouth Bass Micropterus salmoides are the focus of a billion‐dollar (US1 × 10 9 ) recreational fishery in North America and are subject to widespread hatchery supplementation efforts. Parentage‐based tagging (PBT) uses genetic samples taken from hatchery broodstock to genetically "tag" offspring and represents a valuable approach to inform fisheries management and assess hatchery contributions in the wild. This study used a robust microsatellite panel for PBT with Largemouth Bass that reliably discriminated among individuals and siblings and that had low parentage error rates (i.e., false assignments). Genetic data from three cohorts of hatchery broodstock (184 individuals sampled across 3 years) were used to quantify the impacts of planting 150, 346 fingerling Largemouth Bass into Lake Mattamuskeet, North Carolina. Parentage‐based tagging detected low overall levels of hatchery contributions in the wild (4.1%), which varied as a function of collection year (range = 1.5–7.7%). Furthermore, hatchery contributions varied by broodstock cohort, with PBT detections being attributed to broodstock from only two of the three stocking years. The application of PBT for Largemouth Bass represents a cost‐effective and practical approach to tag large numbers of hatchery offspring, monitor supplementation efforts, and evaluate the efficacy of different hatchery practices.